Memorial da Câmara Municipal de Canoas: proposta de plano de gestão estratégico baseado em estudo comparativo de experiências congêneres - Willms, Raquel Gabriela (2014)
This dissertation addresses the issue of institutional memory within the Legislature and its product a proposed Plan Strategic Management, aiming at the creation of the Memorial Hall of Canoas/RS. To this end, we performed a comparative study between programs memory Legislative Houses selected, which are the Legislative Assembly of the State of Rio Grande do Sul and the Municipalities of Porto Alegre and Caxias do Sul, in order to know the work done by these institutions in the areas of memory and culture, in order to subsidize the construction of our proposal. Thus, the Strategic Management Plan was prepared based on relevant theoretical background to the subject, related to the results of studies that were performed and the diagnosis on the status of the City of Canoas. The proposal provides for the creation of the Memorial in order to gather, preserve, manage, and disseminate documentary sets relevant to the history of the institution, develop and update the record of institutional memory and taking action in the community, so that these actions evidence Canoense the importance of Parliament in the context of the history of the City.